2023
DOI: 10.1038/s41598-023-34673-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety profile of intravitreal dexamethasone implant versus antivascular endothelial growth factor treatment in diabetic macular edema: a systematic review and meta-analysis

Abstract: To better understand the efficacy of intravitreal dexamethasone implant (Ozurdex) versus antivascular endothelial growth factor (anti-VEGF) treatment in patients with diabetic macular edema (DME). A systematic review and meta-analysis. The study included randomized control trials (RCTs) and non-randomized control trials (Non-RCTs) before December 2021 that compare the efficacy of Ozurdex-related therapyand anti-VEGF therapy. We searched PubMed, Cochrane Library, and EMBASE. The quality of the included studies … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…However, cataracts in phakic patients negatively impacted visual acuity during the study [ 24 ]. In a systematic review and meta-analysis comparing the efficacy of intravitreal DEX implant (OZURDEX) vs. anti-VEGF therapies, no significant differences in BCVA change were observed between OZURDEX and anti-VEGF therapies in patients with non-resistant DME [ 25 ]. However, when considering baseline central retinal thickness (CRT), the meta-regression analysis indicated that a baseline CRT exceeding 410 µm could be a critical factor influencing the anatomical outcome in favor of OZURDEX therapy [ 25 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…However, cataracts in phakic patients negatively impacted visual acuity during the study [ 24 ]. In a systematic review and meta-analysis comparing the efficacy of intravitreal DEX implant (OZURDEX) vs. anti-VEGF therapies, no significant differences in BCVA change were observed between OZURDEX and anti-VEGF therapies in patients with non-resistant DME [ 25 ]. However, when considering baseline central retinal thickness (CRT), the meta-regression analysis indicated that a baseline CRT exceeding 410 µm could be a critical factor influencing the anatomical outcome in favor of OZURDEX therapy [ 25 ].…”
Section: Reviewmentioning
confidence: 99%
“…In a systematic review and meta-analysis comparing the efficacy of intravitreal DEX implant (OZURDEX) vs. anti-VEGF therapies, no significant differences in BCVA change were observed between OZURDEX and anti-VEGF therapies in patients with non-resistant DME [ 25 ]. However, when considering baseline central retinal thickness (CRT), the meta-regression analysis indicated that a baseline CRT exceeding 410 µm could be a critical factor influencing the anatomical outcome in favor of OZURDEX therapy [ 25 ]. Regarding safety, pooled results from two multicenter, masked, randomized, sham-controlled studies revealed no significant difference in intraocular pressure (IOP) change between the OZURDEX and anti-VEGF groups [ 24 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the comparison of the Ozurdex IV implant and anti-VEGF in DME eyes has shown that Ozurdex is associated with the following: lower BCVA gain [ 107 , 108 , 120 ], which became comparable to anti-VEGF when pseudophakic eyes were analyzed separately [ 107 , 108 , 115 ]; better anatomical results, i.e., higher ability in reducing the macular edema, that did not translate directly into better BCVA improvements [ 107 , 115 , 120 , 121 , 122 , 123 , 124 ], which may be likely due to the cataract development; comparative better results in naïve than in non-naïve eyes, whereas the outcomes in the two groups appear similar in anti-VEGF studies [ 105 ]; better results in chronic and persistent DME eyes and in eyes with moderate-severe DME (CRT > 410 microns) [ 124 , 125 ] better outcomes in real-life studies than in interventional studies [ 126 ]: the possibility of retreating at an earlier stage and the higher number of naïve (2/3 of treatment-naïve eyes in anti-VEGF studies vs. 1/5 in the Ozurdex studies), or short duration DME eyes with better baseline VA in the real-life studies, may explain these differences (on the other hand, systematic review and meta-analysis studies have demonstrated that IV anti-VEGF showed better anatomical and functional results in RCTs compared to the observational studies, likely because fewer injections are administered in the observation studies than those suggested by the RCTs [ 105 , 120 , 126 ], and VA gain seems to be strictly related to the number of the IV injections, at least during the first year of therapy [ 127 , 128 ]); higher risk of OHT, glaucoma, and cataracts and lower risk of serious systemic adverse events [ 107 , 108 , 115 , 119 , 120 , 123 ]; lower number of required IV injections [ 105 , 107 , …”
Section: Corticosteroids For the Management Of Dmementioning
confidence: 99%
“…better anatomical results, i.e., higher ability in reducing the macular edema, that did not translate directly into better BCVA improvements [ 107 , 115 , 120 , 121 , 122 , 123 , 124 ], which may be likely due to the cataract development;…”
Section: Corticosteroids For the Management Of Dmementioning
confidence: 99%